Histomorphological perspectives of preputial and clitoral glands of soft-furred ﬁeld rat Millardia meltada - Rajagopal, Thangavel; Vaideki, Ganesan Ramya; Saibaba, Ganesan; Ponmanickam, Ponnirul; Achiraman, Shanmugam; Rajanarayanan, Swaminathan; Akbarsha, Mohammad Abdulkader; Archunan, Govindaraju (Acta Biologica Szegediensis, 2021)
The present study was an attempt to understand the sexual dimor-phism of the integumentary scent glands of soft-furred field rat Millardia meltada from the perspectives of anatomy, morphology and histology with view to correlate with the sex-specific pheromones they produce. The scent gland of male is known as preputial gland, and female, the clitoral gland. The rats, that are agricultural pests were field caught, the glands of males and females of almost identical size were dissected out, and subjected to gravimetric, morphometric and histological analyses. Both glands are yellowish-brown, pear-shaped, and dorsoventrally compressed. The mean weight, length and width of preputial glands are significantly (p < 0.05) larger than that of the clitoral glands. The preputial gland is composed of sebaceous glandular lobules and apocrine glandular lobules whereas the clitoral gland is formed only of sebaceous glandular lobules. The sebaceous glandular lobules of both preputial and clitoral glands are filled with a wax-like material. Thus, the scent glands of the soft-furred male field rats exhibit sexual dimorphism in respect histoarchitecture of the glands and the nature of the secretory material. This sexual dimorphism of the scent glands may reﬂect control by male and female sex hormones impinging on specific roles as sex attractant pheromones.